If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -2x = 7x + -15 Reorder the terms: 12 + -2x = -15 + 7x Solving 12 + -2x = -15 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 12 + -2x + -7x = -15 + 7x + -7x Combine like terms: -2x + -7x = -9x 12 + -9x = -15 + 7x + -7x Combine like terms: 7x + -7x = 0 12 + -9x = -15 + 0 12 + -9x = -15 Add '-12' to each side of the equation. 12 + -12 + -9x = -15 + -12 Combine like terms: 12 + -12 = 0 0 + -9x = -15 + -12 -9x = -15 + -12 Combine like terms: -15 + -12 = -27 -9x = -27 Divide each side by '-9'. x = 3 Simplifying x = 3
| 5n-9=2n+3 | | -(-4x+6-8)= | | -f(x-2)g=(x^2-3+2) | | 18=k(3) | | -24x+4x^2=0 | | (3x+72)(x-1)= | | 5x=x+26 | | 12h-18=(4h-6) | | 12x-60=0 | | 6(4y-1)=5 | | 2(x+5)=8 | | 3-n=33 | | x-6=(x-4)1/2 | | y=1.5(1) | | V=dt | | 4x^2-8=20 | | 0=1.5x | | 10(-10x+1)= | | 9n^2-50n-80=0 | | -2a+3(4-a)=-3(a+4)-6 | | V=IxR | | 0.4x^3+0.6x^3-0.3x^3= | | x^2+x+20=0 | | -4m=-32 | | x-7=-20 | | 4x-7x(5x-8)=x-8 | | y=-2(1) | | -4(2z+5)=4 | | 5x+9=11+4x | | j-17=2j+13 | | 5x=3x-18 | | n-3n=14-4 |